ISLAM DAN MORAL EKONOMI DALAM PEMIKIRAN SJAFRUDDIN PRAWIRANEGARA - Afif Arrosyid (EPI 16 UMY 049, 2016)
*49 This research aims to describe the thinking from Sjafruddin Prawiranegara in aspects of Islam, Moral economy, biography, and list of his works, the type of this research is (library Research). The nature of this research is a descriptive analysis and analysis techniques used method of qualitative analysis. Research results show that thought from Sjafruddin Prawiranegara in the aspect of Islam as follows: 1) Islam as the Foundation of Muslim power base in maintaining, managing and optimizing the wealth. 2) the power of as unifying the nation of Indonesia. 3) in the spirit of unity, Islamic influence economic moral so on 24 July 1967 has stood the Set Entrepreneur Muslim of Indonesia. On his thoughts about moral of Islamic Economics has principles as follows: social justice, welfare, balance, and family. Then the thinking from Sjafruddin Prawirnegara about the islamic economy evolves in several aspects: 1) the Islamic economic system is that economic principles in the influence of the teachings of Islam. Aims to create a concept that can provide well-being. 2) Islamic Economics into the middle way against the problems faced by the community who embraced Capitalist and Socialist economics. Islamic Economics provides an fundamentally understanding of the importance of moral in conducting economic activities. 3) interest is not identical with usury because the concept of interest is the same as the rent of money which take advantage of the deal and the absence of coercion against fellow. Keywords: Islam, Moral economy, biography, works, the Moral Economy of Islam and Islamic Economics.